Liquid packaging paperboard

The problem of cracking of liquid packaging paperboard during folding and forming is solved by using chemical thermal grinding mechanical pulp and hydrophobic adhesives, and combining the printing layer and back layer at high volt roller pressing dryness. , improves the tensile strength and stability of cardboard.

CN119301324APending Publication Date: 2025-01-10BILLERUD AB
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380044081.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-02
Filing Date
2023-05-31
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

There is a risk of cracking during the folding and forming process of liquid packaging cardboard, affecting the reliability of its conversion into packaging.

Method used

The intermediate layer of paper is formed by chemical thermal grinding mechanical pulp (CTMP) and hydrophobic rubber, and the printing layer and back layer are combined with the intermediate layer by a volt roller press dryness of more than 10%, reducing the strength of the interface, thereby Reduce the risk of cracking during folding.

Benefits of technology

It effectively reduces the cracking trend of liquid packaging cardboard during folding and forming, improves the z-direction tensile strength and tensile index of cardboard, and enhances its stability during indentation and folding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119301324A_ABST
    Figure CN119301324A_ABST
Patent Text Reader

Abstract

There is provided a method of producing a multilayer liquid packaging paperboard (LPB) comprising a printed layer, a back layer and an intermediate layer, the method comprising the steps of:-providing a chemical thermo-mechanical pulp (CTMP) and forming an intermediate layer paper stock comprising CTMP and a hydrophobic sizing; forming an intermediate layer web from the intermediate layer paper stock in a forming section of the full-size cardboard machine; -in the forming section, forming a printed layer web from a printed layer paper stock, the printed layer paper stock comprising a hydrophobic sizing; -in the forming section, forming a backing web from a backing paper stock, the printed layer paper stock comprising a hydrophobic sizing; combining the printed layer web with the intermediate layer web by couch press at a couch press dryness of greater than 10%, such as greater than 13%, where the z strength of the CTMP is at least 150 kPa, such as at least 180 kPa, when measured according to ISO 15754: 2009, after sheet forming according to ISO 5269-2: 2004.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of manufacturing liquid packaging paperboard. Background Art

[0002] Liquid packaging board (LPB) is an engineered material that is typically made up of different layers and interfaces. This creates an out-of-plane (z) profile that can be designed for optimal functionality or cost effectiveness. Commercial LPB typically has a relatively bulky middle ply to achieve high bending stiffness with a low fiber count.

[0003] Creasing and subsequent folding are necessary to convert the LPB into packaging. In the creasing operation, a male ruler is pressed against the cardboard located on top of the female mold. The purpose of the creasing operation is to facilitate the subsequent folding. However, during the folding and forming process, there is a risk of cracking. Summary of the invention

[0004] It is an object of the present disclosure to provide a method for reducing the tendency of LPB to crack during the folding and forming process.

[0005] Therefore, the present disclosure provides a method for producing a multi-layer liquid packaging board (LPB), the multi-layer liquid packaging board comprising a printing layer, a back layer and an intermediate layer, the method comprising the following steps:

[0006] - providing a chemical thermomechanical pulp (CTMP) and forming an intermediate layer stock comprising the CTMP and a hydrophobic size;

[0007] - forming an intermediate layer web from said intermediate layer stock in a forming section of a full-size board machine;

[0008] - in the forming section, forming a printing layer web from a printing layer stock, the printing layer stock comprising a hydrophobic size;

[0009] - in the forming section, forming a backing layer web from a backing layer stock, wherein the printing layer stock comprises a hydrophobic sizing material;

[0010] - merging the printing layer web with the intermediate layer web by couching, preferably at a couch dryness of above 10%, such as above 13%,

[0011] Wherein, the CTMP has a z-strength of at least 150 kPa, such as at least 180 kPa, when measured according to ISO 15754:2009 after sheet formation according to ISO 5269-2:2004. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 It shows that from the production of 290g / m 2Test results for samples obtained during machine tests on a three-ply (non-LPB) board having an intermediate layer formed from a stock comprising 45% CTMP, 45% broke pulp and 10% kraft pulp. During one period of the test, the amount of spray starch applied in the print layer / intermediate layer interface was 0.83 g / m 2 During another period of the test, the amount of spray starch applied in the print layer / intermediate layer interface was 1.05 g / m 2 For each quantity, Figure 1 Shows the proportion of samples that failed in:

[0013] (i) printed layer / interlayer interface (“PL interface”);

[0014] (ii) middle layer (“ML”);

[0015] (iii) back layer / middle layer interface ("BL interface"); and

[0016] (iv) Two interfaces ("double layer").

[0017] Figure 2 The Scott binding test results of samples obtained from the reference test (n=50) and the test of the present invention (n=25) are shown. In detail, Figure 2 The failure point for each test sample is presented, ie where the paperboard broke in the z-direction during the Scott Bond test. Figure 2 The abbreviations used in Figure 1 Explained.

[0018] Figure 3 The shear strength distribution in the z-direction is shown for boards produced in a high-dryness run and a low-dryness run. Figure 3 The abbreviations used in Figure 1 Explained. DETAILED DESCRIPTION

[0019] The present disclosure provides a method for producing a multi-layer liquid packaging board (LPB), the multi-layer liquid packaging board comprising a printing layer, a backing layer and an intermediate layer. As understood by those skilled in the art, the intermediate layer is arranged between the printing layer and the backing layer.

[0020] The method comprises the following steps:

[0021] - providing CTMP and forming an intermediate layer stock comprising CTMP and a hydrophobic size;

[0022] - forming an intermediate layer web from the intermediate layer stock in the forming section of a full-size board machine;

[0023] - in a forming section, forming a printing layer web from a printing layer stock, the printing layer stock comprising a hydrophobic size; and

[0024] - In the forming section, a backing web is formed from a backing stock, the printing stock comprising a hydrophobic size.

[0025] The presence of a hydrophobic size in each of the above mentioned paper stocks is typical for the process of making LPB.

[0026] The amount of hydrophobic size in each of the print layer stock and the backing layer stock is preferably at least 1.5 kg / ton of dry fiber, such as at least 2.0 kg / ton of dry fiber.

[0027] The amount of hydrophobic size in the middle layer paper stock is usually greater than the amount of hydrophobic size in any one of the printing layer paper stock and the backing layer paper stock. For example, it can be at least 2.5 kg / ton of dry fiber, such as at least 3.0 kg / ton of dry fiber.

[0028] The hydrophobic size in each of the printing layer stock, the backing layer stock and the middle layer stock can be, for example, independently selected from the group consisting of alkenyl succinic anhydride (ASA), alkyl ketene dimer (AKD), rosin size and a combination thereof. In a preferred embodiment, the hydrophobic size in each stock is a combination of AKD and rosin size. When this combination is used, the headbox pH of the stock is preferably in the range of 6.6-7.2, such as 6.9-7.1.

[0029] The printing layer web is combined with the middle layer web by couch roll lamination. It is preferably carried out at a couch roll lamination dryness higher than 10%, such as higher than 13%, to reduce the strength of the interface between the printing layer and the middle layer, thereby avoiding delamination in the middle layer during folding. Here, couch roll lamination dryness refers to the dryness of the printing layer web just before couch roll lamination. In one embodiment, both the printing layer web and the middle layer web have a dryness higher than 10%, such as higher than 13%, just before couch roll lamination.

[0030] Preferably, the back web is also combined with the middle web by couch roll lamination at a couch roll lamination dryness higher than 10% (preferably higher than 13%) to reduce the strength of the interface between the back web and the middle web. Here, couch roll lamination dryness refers to the dryness of the back web just before couch roll lamination. In one embodiment, both the back web and the middle web have a dryness higher than 10%, such as higher than 13%, just before couch roll lamination.

[0031] After sheeting according to ISO 5269-2:2004, the z-direction tensile strength ("z-strength") of the CTMP is at least 150 kPa, such as at least 180 kPa, when measured according to ISO 15754:2009 (a suitable upper limit for this z-strength may be 250 kPa). Thus, the risk of delamination (and hence the risk of cracking, see below) in the interlayer is reduced. For the same reason, after sheeting according to ISO 5269-1:2005, the tensile index of the CTMP is preferably above 15 Nm / g, such as above 17 Nm / g, when measured according to ISO 1924-3:2005. Rapid- An automatic sheet forming machine is preferably used to perform the sheet forming. "Tensile Index" is the tensile strength obtained by ISO 1924:3:2005 divided by the grammage. The grammage is measured according to ISO 536:2019. The z-strength of CTMP can be increased by beating the CTMP.

[0032] In one embodiment, the CSF of the CTMP of the interlayer stock is below 600 ml, such as 500-580 ml, when measured according to ISO 5267-2:2001. Such relatively low CSF values ​​are associated with a favorable ratio of interlayer strength to interface strength in the z-direction.

[0033] In order to achieve bulk, the proportion of CTMP in the middle layer paper stock is preferably higher than 20% by dry weight, such as higher than 30% by dry weight, such as at least 32% by dry weight. In some embodiments, it may be preferred to keep the proportion of CTMP in the middle layer paper stock below 45% (e.g., 42% or lower) to prevent the Scott bonding value from being too low. Therefore, the proportion of CTMP in the middle layer paper stock may be in any of the following ranges: higher than 20%, but lower than 45%; higher than 20%, but not more than 42%; higher than 30%, but lower than 45%; higher than 30%, but not more than 42%; at least 32%, but lower than 45%; or at least 32%, but not more than 42%.

[0034] In addition to CTMP, the middle layer stock preferably comprises broke pulp. Broken pulp may be obtained from LPB production formed as part of the disclosed process. The proportion of broke pulp in the middle layer stock is generally in the range of 10%-50%, preferably 10%-35%, more preferably 20%-33%.

[0035] Furthermore, the middle layer stock preferably comprises chemical pulp, such as kraft pulp, preferably softwood kraft pulp. This chemical pulp may be bleached or unbleached. A particularly preferred type of chemical pulp is bleached softwood kraft pulp. The proportion of chemical pulp in the middle layer stock is typically in the range of 10%-50%, such as 20%-40%. One reason for including chemical pulp, preferably softwood kraft pulp, which is a relatively strong pulp type, is to balance CTMP, which is a relatively weak pulp type.

[0036] A suitable Schopper-Riegler (SR) number for the middle layer stock is °18-°23. Such a SR number can be obtained by adjusting the degree of beating of the individual pulps forming the middle layer stock. The SR number is measured according to ISO 5267-1:1999.

[0037] The z-strength of the interlayer stock is preferably at least 375 kPa, such as at least 415 kPa, when measured according to ISO 15754:2009 after sheet formation according to ISO 5269-2:2004. A suitable upper limit is 545 kPa, such as 495 kPa.

[0038] In one embodiment, the CTMP provided is obtained by post-pulping CTMP from a CTMP production process. As will be appreciated, this post-pulping is carried out in the wet section of the LPB production process. However, the degree of post-pulping is preferably low, for example less than 30 kWh / ton of dry fiber.

[0039] In production 290g / m 2 Machine trials conducted during the printing of three-ply (non-LPB) paperboards, the middle ply of which was formed from a stock comprising 45% CTMP, 45% broke and 10% kraft pulp, showed that the amount of spray starch applied in the print layer / middle layer interface increased from 0.83 g / m 2 Increased to 1.05 g / m 2 This resulted in a reduction in the failure rate during the Scott bond test at this interface from 100% to approximately 45% (see Figure 1 ). Therefore, in one embodiment of the method, less than 1 g / m 2 , such as less than 0.9g / m 2 Therefore, in one embodiment of the method, no starch is provided in the interface between the printing layer web and the intermediate layer web. Alternatively, more than 0.2 g / m 2 of starch is provided in the interface between the printing layer web and the intermediate layer web. 2 , such as more than 0.3g / m 2Therefore, in one embodiment, less than 1 g / m 2 of starch is provided in the interface between the printing layer web and the intermediate layer web. 2 And more than 0.2g / m 2 Starch, such as less than 0.9 g / m 2 And more than 0.3g / m 2 For the avoidance of doubt, this does not include starch added to any stock upstream of the headbox.

[0040] In addition, less than 1 g / m2 can be provided in the interface between the back web and the middle web. 2 , such as less than 0.9g / m 2 Thus, in one embodiment of the method, no starch is provided in the interface between the printing layer web and the intermediate layer web. For the avoidance of doubt, this does not include starch in any stock added upstream of the headbox.

[0041] The method may include the step of coating the printed layer with at least one coating layer. The at least one coating layer is typically pigment-based. The total coating weight (dry weight) may be 12-30 g / m 2 .

[0042] The basis weight of the multilayer LPB (including any pigment-based coating) produced by this method may be, for example, 150-350 g / m 2 , preferably 210-310g / m 2 The basis weight of the printed layer (excluding any pigment-based coating) can be 45-90 g / m 2 , such as 55-80g / m 2 The weight of the back layer can be 40-70g / m 2 , such as 40-65g / m 2 Basis weight (also called grammage) is measured according to ISO536:2019.

[0043] The density of the multilayer LPB produced by this method can be, for example, 650-750 g / m 2 . Density is measured according to ISO 534:2011.

[0044] The z-strength of the multilayer LPB produced by this method may for example be 280-415 kPa, such as 300-400 kPa. The z-strength is measured according to ISO 15754:2009.

[0045] The Scott bond strength of the multilayer LPB produced by this method may be, for example, 145-305, such as 170-250 kPa. The Scott bond strength is measured according to TAPPI T 569om-09.

[0046] Example

[0047] Reference test

[0048] Three-layer liquid packaging board (LPB) is produced in a full-size board machine. The layer design of LPB is as follows: bleached printing layer (65g / m 2 ), unbleached backing layer (60g / m 2 )、Middle layer (125g / m 2 ) and a pigment coating (19 g / m 2 ).

[0049] To prepare the printing layer stock, bleached hardwood kraft pulp (NBHK) and bleached softwood kraft pulp (NBSK) were mixed in a dry weight ratio of 60:40. Before mixing, NBHK and NBSK were LC-beaten (65 and 150 kWh / ton, respectively) so that both pulps obtained a °SR value of about 32. Before the printing layer headbox, rosin size (1.5 kg / ton), AKD (1 kg / ton), alum (2.3 kg / ton), reinforcing agent (cationic starch, 2.5 kg / ton), retention starch (3 kg / ton), retention polymer (100 g / ton) and silica (300 g / ton) were added. In the printing layer headbox, the consistency was 0.19% and the pH was 6.8.

[0050] The back layer stock was prepared from unbleached softwood kraft pulp (UBK) which had been subjected to LC beating (100 kWh / ton) to obtain a °SR value of about 23. Before the back layer headbox, rosin size (1.5 kg / ton), AKD (1 kg / ton), alum (1.5 kg / ton), strengthening agent (cationic starch, 2.5 kg / ton), retention starch (3 kg / ton), retention polymer (100 g / ton) and silica (300 g / ton) were added. In the bottom headbox, the consistency was 0.18% and the pH was 6.8.

[0051] For the preparation of the middle layer stock, broke pulp, NBSK and CTMP were used in a dry weight ratio of 30:35:35. CTMP had a tensile index of about 13-14 Nm / g (when measured according to ISO 1924-3 after sheet formation according to ISO 5269-1:2005). Before mixing, the pulps were subjected to LC beating to obtain the following values: about °SR 30 for broke pulp (beating energy: about 20 kWh / ton); about °SR 23 for NBSK (beating energy: about 100 kWh / ton); and about CSF 550 ml for CTMP (beating energy: about 20 kWh / ton). Before the middle layer headbox, rosin size (2.5 kg / ton), AKD (2.5 kg / ton), alum (3.8 kg / ton), reinforcing agent (cationic starch, 2.5 kg / ton), retention starch (3 kg / ton), retention polymer (100 g / ton) and silica (300 g / ton) were added. In the middle layer headbox, the consistency was 0.41% and the pH was 6.8. The forming wire for forming the middle layer includes, for example, a top wire former and a breast roll vibrator.

[0052] In the wire section (forming wire speed = 623 m / min), starch (0.7 g / m 2 ) is sprayed into each of the printing layer web and the backing layer web. At the end of the wire section, the three individual webs (the starch spray side of the outer webs faces the middle web) are couch-rolled together to form a three-layer web. At the couch-rolling stage, the dry matter content of each web is about 14%-16%. In the press section placed downstream of the wire section, the three-layer web is pressed in three press zones; the first double felt shoe press press zone (450 kN / m), followed by the second double felt shoe press press zone (600 kN / m) and the hard press zone (50 kN / m).

[0053] Downstream of the press section, the three-layer web was dried in a drying section and then calendered in a hard nip calender at a line load of 20 kN / m and a temperature of 240°C. After calendering, the web was coated in a coating section with several coating stations. At the blade coating station, 7.5 g / m 2 The pigment coating composition is applied to the surface of the printed layer. At another station, which is a metered size press (MSP), a small amount (0.4 g / m 2 ) of starch was applied to the back surface. In the second blade coating station, another 11.5 g / m 2 The pigment coating composition is applied to the upper surface. Thus, a total of 19 g / m 2 Coated onto the printed surface, and a total of 0.4 g / m 2 Apply to the back surface.

[0054] Invention test

[0055] Three-layer liquid packaging board (LPB) is produced in a full-size board machine. The layer design of LPB is as follows: bleached printing layer (65g / m 2 ), unbleached backing layer (50g / m 2 )、Middle layer (125g / m 2 ) and a pigment coating (19 g / m 2 ).

[0056] To prepare the printing layer stock, bleached hardwood kraft pulp (NBHK) and bleached softwood kraft pulp (NBSK) were mixed in a dry weight ratio of 30:70. Before mixing, NBHK and NBSK were LC-pulped (50 and 120 kWh / ton, respectively) to obtain °SR values ​​of 28 and 25 for the two pulps, respectively. Before the printing layer headbox, rosin size (1.5 kg / ton), AKD (1.5 kg / ton), alum (2.3 kg / ton), reinforcing agent (cationic starch, 2.5 kg / ton), retention starch (3 kg / ton), retention polymer (50 g / ton) and silica (150 g / ton) were added. In the printing layer headbox, the consistency was 0.19% and the pH was 7.0.

[0057] The back layer stock was prepared from unbleached softwood kraft pulp (UBK) which had been subjected to LC beating (100 kWh / ton) to obtain a °SR value of about 23. Before the back layer headbox, rosin size (1.5 kg / ton), AKD (1 kg / ton), alum (1.5 kg / ton), strengthening agent (cationic starch, 2.5 kg / ton), retention starch (3 kg / ton), retention polymer (100 g / ton) and silica (300 g / ton) were added. In the bottom headbox, the consistency was 0.18% and the pH was 7.0.

[0058] For the preparation of the middle layer stock, broke pulp, NBSK and CTMP were used in a dry weight ratio of 30:35:35. CTMP had a tensile index of about 18-19 Nm / g (when measured according to ISO 1924-3 after sheet formation according to ISO 5269-1:2005). Before mixing, the pulps were subjected to LC beating to obtain the following values: about °SR 30 for broke pulp (beating energy: about 10-20 kWh / ton); about °SR 23 for NBSK (beating energy: about 100 kWh / ton); and about CSF 560-565 ml for CTMP (beating energy: about 10-20 kWh / ton). The approximate properties of the CTMP and the stock (containing all three pulps) after beating are provided in the following Table 1. Before the middle layer headbox, rosin size (2.5 kg / ton), AKD (2.5 kg / ton), alum (3.8 kg / ton), reinforcing agent (cationic starch, 1 kg / ton), retention starch (3 kg / ton), retention polymer (75 g / ton) and silica (225 g / ton) were added. In the middle layer headbox, the consistency was 0.37% and the pH was 7.0. The forming wire for forming the middle layer includes, for example, a top wire former and a breast roll vibrator.

[0059] Table 1. Approximate properties of beaten CTMP and interlayer stocks measured after sheet formation according to ISO 5269-2:2004.

[0060] CTMP Middle layer paper Thickness [μm] 196 172 <![CDATA[Grammage [g / m 2 > 96 102 <![CDATA[Density [kg / m 3 > 492 595 Tensile strength [kN / m] 1.8 4.2 Tensile stiffness [kN / m] 373 578 Fracture strain [%] 0.65 1.60 <![CDATA[Tensile Energy Absorption (TEA) [J / m 2 > 7.7 48.6 Z strength [kPa] 207 455 <![CDATA[Scott combination [J / m 2 > 55 248

[0061] In the wire section (forming wire speed = 623 m / min), starch (0.7 g / m 2 ) was sprayed into each of the printing layer web and the backing layer web. At the end of the wire section, the three individual webs (the starch sprayed side of the outer webs facing the middle web) were couch-rolled together to form a three-layer web. At the couch-rolling stage, the dry matter content of each web was about 14%-16%. In the press section placed downstream of the wire section, the three-layer web was pressed in three press zones; the first double felt shoe press press zone (390 kN / m), followed by the second double felt shoe press press zone (460 kN / m) and the hard press zone (50 kN / m).

[0062] Downstream of the press section, the three-layer web was dried in a drying section and then calendered in a hard nip calender at a line load of 20 kN / m and a temperature of 240°C. After calendering, the web was coated in a coating section with several coating stations. At the blade coating station, 7.5 g / m 2 The pigment coating composition is applied to the surface of the printed layer. At another station, which is a metered size press (MSP), a small amount (0.4 g / m 2) of starch was applied to the back surface. In the second blade coating station, another 11.5 g / m 2 The pigment coating composition is applied to the upper surface. Thus, a total of 19 g / m 2 Coated onto the printed surface, and a total of 0.4 g / m 2 Apply to the back surface.

[0063] evaluate

[0064] The LPB produced in the reference test and the inventive test were tested according to the Scott bonding method. However, the main interest of the analysis was not the measured Scott bonding value, but the failure point (i.e. where the board broke in the z-direction). In more detail, 50 samples from the reference test and 25 samples from the inventive test were subjected to the Scott bonding test and then visually analyzed and weighed to determine the failure point in the z-direction. The results are presented in Figure 2 , which shows that for samples from the reference test, 80% (40 / 50) of all failures occurred in the interlayer, while only 20% (10 / 50) of the failures occurred at the interlayer / printing layer interface. In contrast, for samples from the invention test, 12% (3 / 25) of all failures occurred in the interlayer, while 88% (22 / 25) of the failures occurred at the interlayer / printing layer interface. It is believed that the main reason for the relocation of failures from inside the interlayer to the interlayer / printing layer interface is the change in CTMP quality. In addition, it is known from earlier studies that delamination in the interface rather than in the interlayer significantly reduces the tendency to crack during conversion to LPB packaging ( et al.,PAPERPHYSICS,Nordic Pulp&Paper Research Journal Vol 29no(3)2014).

[0065] Couch roller pressing dryness test

[0066] To test the effect of web dryness at the couch roll lamination stage, the results of two full-scale machine runs were compared. In one run, the dryness of each web was about 16% ("high dryness run"), while in the other run, the dryness of the back and middle layer webs was still about 16%, while the dryness of the print layer web was about 7% ("low dryness run"). Apart from this, the operating conditions of the two machine runs were approximately the same as those of the above-mentioned inventive test.

[0067] according to et al. (see above for full reference) established the shear strength distribution in the z direction for boards produced in high and low dryness runs. Figure 3, which shows that running at low dryness results in an interlayer / print layer interface with significantly higher strength.

Claims

1. A method for producing a multi-layer liquid packaging board (LPB), the multi-layer liquid packaging board comprising a printing layer, a back layer and an intermediate layer, the method comprising the following steps: - providing a chemical thermomechanical pulp (CTMP) and forming an intermediate layer stock comprising the CTMP, broke pulp and a hydrophobic size; - forming an intermediate layer web from said intermediate layer stock in a forming section of a full-size board machine; - in the forming section, forming a printing layer web from a printing layer stock, the printing layer stock comprising a hydrophobic size; - in the forming section, forming a backing layer web from a backing layer stock, wherein the printing layer stock comprises a hydrophobic sizing material; - merging the printing layer web with the intermediate layer web by couch roll lamination at a couch roll dryness above 10%, such as above 13%, Wherein, the CTMP has a z-strength of at least 150 kPa, such as at least 180 kPa, when measured according to ISO 15754:2009 after sheet formation according to ISO 5269-2:2004.

2. The method according to claim 1, wherein: After sheet formation according to ISO 5269-1:2005, the CTMP has a tensile index of above 15 Nm / g, such as above 17 Nm / g, when measured according to ISO 1924-3.

3. The method according to claim 1 or 2, wherein: The CSF of the CTMP is less than 600 ml, such as 500-580 ml, when measured according to ISO 5267-2:2001.

4. A method according to any one of the preceding claims, wherein: The proportion of CTMP in the middle layer stock is higher than 20% by dry weight, and preferably lower than 45% by dry weight.

5. A method according to any one of the preceding claims, wherein: The proportion of CTMP in the middle layer stock is higher than 30% by dry weight, such as 32%-42% by dry weight.

6. A method according to any one of the preceding claims, wherein: The proportion of broke pulp in the middle layer stock is less than 35%, such as 20%-33%.

7. A method according to any one of the preceding claims, wherein: The middle layer paper stock further comprises softwood kraft pulp.

8. The method according to claim 7, wherein: The proportion of softwood kraft pulp in the middle layer of paper stock is 20%-40%.

9. A method according to any one of the preceding claims, wherein: The Schober-Riegler number of the middle layer paper stock is 18-23.

10. A method according to any one of the preceding claims, wherein: The interlayer stock has a z-strength of at least 375 kPa, such as at least 415 kPa, when measured according to ISO 15754:2009 after sheet formation according to ISO 5269-2:2004.

11. A method according to any one of the preceding claims, wherein: The provided CTMP is obtained by post-beating CTMP from a CTMP production process.

12. A method according to any one of the preceding claims, wherein: Providing less than 1 g / m2 in the interface between the printing layer web and the intermediate layer web 2 , such as less than 0.9g / m 2 of starch.

13. A method according to any one of the preceding claims, wherein: The amount of hydrophobic size in the printing layer stock is at least 1.5 kg / ton of dry fiber, such as at least 1.5 kg / ton of dry fiber.

14. A method according to any one of the preceding claims, wherein: The amount of hydrophobic size in the backing paper stock is at least 1.5 kg / ton of dry fiber, such as at least 2.0 kg / ton of dry fiber.

15. A method according to any one of the preceding claims, wherein: The amount of hydrophobic size in the middle layer stock is at least 2.5 kg / ton of dry fiber, such as at least 3.5 kg / ton of dry fiber.

16. A method according to any one of the preceding claims, wherein: The hydrophobic size in the printing layer paper stock is selected from the group consisting of ASA, AKD, rosin size and combinations thereof; The hydrophobic size in the backing paper is selected from the group consisting of ASA, AKD, rosin size and combinations thereof; and / or The hydrophobic size in the middle layer paper stock is selected from the group consisting of ASA, AKD, rosin size and combinations thereof.